Preparation, Optimization and Characterization of Bovine Lactoferrin‐loaded Liposomes and Solid Lipid Particles Modified by Hydrophilic Polymers Using Factorial Design. (14th March 2014) - Yao, Xudong; Bunt, Craig; Cornish, Jillian; Quek, Siew‐Young; Wen, Jingyuan
<x xml:space="preserve">Abstract</x> Bioadhesive liposomes and solid lipid particles (SLPs) modified by pectin and chitosan for oral administration of bovine lactoferrin (bLf) were prepared using a 24 full‐factorial design to identify the key formulation variables influencing particle size and drug entrapment efficiency (EE). Netlike structures of the polymer–particle mixture consisting of a polymeric network in which multiple particles were imbedded were observed by scanning electron microscopy (SEM). Chemical stability of bLf after encapsulation into pectin‐ and chitosan‐modified liposomes and SLPs was confirmed by Fourier transform infrared spectra (FTIR). Bovine lactoferrin was located within phospholipid bilayer, whereas in SLPs bLf was within the matrix. The crystalline nature of bLf after encapsulation was investigated by differential scanning calorimetry (DSC) of drug‐loaded particles, indicating amorphous dispersion of bLf in the polymer–lipid matrix of pectin‐ and chitosan‐modified liposomes and SLPs. In vivo pharmacokinetic investigation of bLf in pectin‐ and chitosan‐modified liposomes and SLPs showed prolonged mean residence time (MRT) of bLf in rat blood and increased the relative bioavailability (Fbio%) by 1.95‐ to 2.69‐fold compared with free bLf. The developed carrier systems are considered to be promising vehicles for oral delivery.